Real‐world effectiveness and tolerability of cenobamate in drug‐resistant epilepsy: A retrospective analysis of the patients included into the Early Access Programs (EAP) in Germany, France, and United Kingdom - Sylvain Rheims; Bernhard J. Steinhoff; Edouard Hirsch; Felix Rosenow; Arnaud Biraben; Rhys Thomas; Alessandro Lovera; Paola Lipone; Alessandro Comandini; Caroline Benoist; Elena Alvarez Baron; John Paul Leach; et al. (Epilepsia Open)
Abstract Objective Investigate real‐world outcomes in drug‐resistant epilepsy (DRE) patients treated with cenobamate as adjunctive treatment to other antiseizure medications (ASMs) within the Early Access Programs (EAP) in Germany, France, and the United Kingdom. Methods DRE adults with uncontrolled focal‐onset seizures were included from 19 hospitals participating in the EAP in this retrospective study. Data were sourced from clinical records. Participants were evaluated at baseline, 1 months, and 3 months from cenobamate start, and 3, 6, and 12 months after maintenance. The primary effectiveness endpoint was the 50% responder rate, defined as the reduction in seizure frequency ≥50%. Results Data were collected from 298 patients who received at least one dose of cenobamate; efficacy was evaluated on 216 patients with seizure data available. At baseline, the median epilepsy duration was 22.2 years, and 41.9% of patients had previous epilepsy surgery, including vagus nerve stimulation, with a median of nine previously failed ASMs. The median number of seizures/month was 8.8. After 3 months of maintenance, the 50% responder rate (primary endpoint) was 49.3%; the median percentage seizure reduction from baseline was 49.1%. A total of 100%, ≥90%, and ≥75% seizures reduction were reported in 13.6%, 20.0%, and 33.6% of patients, respectively. Both the responder rate and the median percentage seizure reduction steadily increased during the observation period. At 6‐month maintenance, the seizure‐free rate was 24.2%. The retention rate assessed by Kaplan–Meier decreased from 96.6% at 1‐month cenobamate start to 69.7% at 12‐month maintenance. Adverse Drug Reactions (ADRs) to cenobamate occurred in 30.9% of patients, with asthenia, dizziness, and somnolence being the most frequent; the majority were mild‐to‐moderate and resolved during the observation period; three patients (1.0%) experienced a total of seven serious ADRs, all during titration. Significance In this study, cenobamate demonstrated to be an effective option for people with uncontrolled epilepsy even after multiple failed ASMs or failure of epilepsy surgery. Plain Language Summary This study involved patients with drug‐resistant epilepsy, who had continued seizures despite using at least two antiseizure medications (ASMs). Patients received cenobamate (Ontozry) as epilepsy treatment during the Early Access Program (EAP) in France, Germany, and the United Kingdom. An EAP allows patients to receive promising new drugs under clinical supervision before they are commercially available. After 6 months from cenobamate start, 49.3% of patients had their seizures cut by half or more, and 13.6% became seizure‐free. A total of 30.9% of patients had an undesirable reaction to cenobamate, mostly mild‐to‐moderate and resolved; the most frequent were asthenia, dizziness, and somnolence.